Ethanol adsorption on SrTiO3 surfaces - Stashans, A. (2006)
Using a quantum chemical method developed for crystalline systems and a periodic large unit cell (LUC) model, ethanol, CH3CH2OH, adsorption on the SrTiO3 (001) surfaces is studied, considering both cubic and tetragonal lattices of the crystal. The investigation is carried out for the ethanol molecule as a whole complex and considering its decomposition into the ethylene and water. The structural and electronic effects involved in the adsorption are discussed. The obtained results predict a higher possibility of ethanol adsorption on the Ti-O2 face of the SrTiO3 (001) surfaces for both crystallographic lattices. The favored ethanol adsorption as a whole complex testifies the possibility of the ethanol molecule formation from the ethylene and water on the SrTiO3 (001) surface with the former acting as a catalyst. © 2006 Wiley Periodicals, Inc.